Sustainable forestry investment under the clean development mechanism: The Malaysian case - Michael Dutschke (Hamburg Institute of International Economics (HWWA), 2002)
In the light of the development of the Malaysian forestry sector in recent years, the article gives an overview over the current discussions around the inclusion of biological carbon sink projects under the Clean Development Mechanism (CDM) of the Kyoto Protocol, like forest definitions, additionality, baselines and permanence. Some new ideas are presented, the details of which need to be explored in detail in further studies. As a result, the article gives twofold recommendations: First, which issues international climate negotiators need to tackle in order to make forestry projects work in practice; and second, how and under which conditions CDM forestry can be supportive to the Malaysian development goals. – – Vor dem Hintergrund der Entwicklung des malaysischen Forstsektors in den letzten Jahren gibt der vorliegende Aufsatz einen Überblick über die aktuellen Diskussionen um die Einbeziehung biologischer Kohlenstoffsenken in den Clean Development Mechanism (CDM) des Kyoto-Protokolls. Stichwörter sind Forstdefinitionen, Zusätzlichkeit, Baselines und Permanenz. Der Autor unterbreitet in diesem Zusammenhang einige neue Vorschläge, deren Details Gegenstand künftiger Studien sein werden. Zusammenfassend gibt der Artikel Politikempfehlungen auf zwei Ebenen: Zum einen, welche Fragen die internationalen Verhandlungsführer lösen müssen, bevor Forstprojekte unter dem CDM zur Realität werden können. Zum anderen, wie und unter welchen Bedingungen CDM-Forstwirtschaft den malaysischen Entwicklungszielen zuträglich sein kann.
Keywords: 330; Forstpolitik; Aufforstung; Klimaschutz; Entwicklungshilfe; Malaysia; Kohlenstoffsenke